Character portrayal and Malay women characters in Malay classsical cinema during studio era: ‘Musang Berjanggut’ (1959), ‘Tun Fatimah’ (1962) / Muhammat Md Noh and Mastura Muhammad - Md Noh, Muhammat; Muhammad, Mastura (Universiti Teknologi Mara Cawangan Pulau Pinang, 2021)
The research explores the representation of the image of Malay female characters in two classical Malay films that were produced during the studio era, which is Musang Berjanggut (1959) and Tun Fatimah (1962). Through the application of the gender concept as a performance "Gender is Performativity" by Judith Butler, the focus of the analysis was towards two traditional main Malay female characters, Puspawangi and Tun Fatimah. The concept of gender as a performance was analysed through the perspectives of custom and traditional culture of Malay society that became an aid in forming the image of the characters and characteristics that were analysed. The research found that both of the main characters in the classical text that were studied were influenced by the custom and traditional culture that maintained the stereotype of the character and that limits the autonomy and the domination of the traditional female within the society. The research also found that although the custom and the traditional Malay culture at its foundation does celebrate the nature of the traditional woman that was seen and perceived as passive, the pattern and the pole of the position of the characters and characteristics in both of the films does change depending on the situation, timeline and the background of their surroundings. Taking everything into consideration, the women that were studied does have the dynamic that contributes towards the representation of the Malay women that is more progressive and had more roles as the mover of the narrative in the film that was studied.